Old Main Bell: final design report - Bushlack, Blake, author; Toebe, Jason, author (Colorado State University. Libraries, 2024)
Due to varying age and physical abilities of Alumni from Colorado State University, access to ringing the Old Main Bell was limited, in some cases requiring family members to step in for elderly Alumni. To accommodate these different skill levels of users, a ratchet system was implemented to pre-load the Bell, storing potential energy which will be converted to kinetic energy when the ratchet is released. All of this was done to preserve the historic motion of ringing the Bell while simplifying the task. Additionally, the system can be operated without the ratchet to allow for the user to choose how to ring the Bell and in doing so improve the lifespan of the rope by reducing friction applied to it.
Old Main Bell - senior design project
Colorado State University. Walter Scott, Jr. College of Engineering, Department of Mechanical Engineering, University Honors Program Foundational.
Report by Blake Bushlack and Jason Toebe. Project Advisor: Wade Troxell, Ph.D. Project Commitee Member: Mitchell Stansloski, Ph.D., PE.